Exploring biochemical, extraction, and catalytic processes for sustainable sesame crop valorization in biorefinery applications - Juan M. González; Fabiana Franceschi; Karina Ojeda-Delgado; Eduardo Sánchez-Tuirán (Frontiers in Sustainable Food Systems)
The transition from fossil-based to bio-based chemicals and fuels is essential to mitigate environmental impacts and promote sustainability. Sesame (Sesamun indicum L.), a widely used oilseed crop, presents significant potential for biorefinery applications due to its high oil content, valuable bioactive compounds, and abundant lignocellulosic biomass. This review explores recent advances in bio-based, extraction, and catalytic processes for the integral valorization of sesame crops. Bio-based conversion routes, including anaerobic digestion and fermentation, enable the sustainable production of biofuels such as biogas, ethanol, and biodiesel. Advanced extraction techniques facilitate the recovery of high-value compounds, namely lignans and proteins, for use in pharmaceuticals and functional foods. Catalytic processes, such as transesterification and epoxidation, further expand the potential of sesame oil for bioplastics, polyurethane production, and biofuel synthesis. The novelty of this review lies in providing the first integrated assessment of sesame valorization pathways within a biorefinery framework, highlighting unexplored synergies across energy, materials, and nutraceutical applications. Key challenges such as process scalability, cost-efficiency, and environmental trade-offs were identified as critical barriers to large-scale implementation. Addressing these gaps can guide future research efforts and inform policymakers, ultimately creating economic opportunities for farmers, reducing reliance on fossil fuels, and promoting circular bio-economy models based on sesame and similar crops.